2019
DOI: 10.1002/jlb.ma1118-471r
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage priming is dispensable for NLRP3 inflammasome activation and restriction of Leishmania amazonensis replication

Abstract: The NLRP3 inflammasome is activated in response to multiple stimuli and triggers activation of caspase‐1 (CASP1), IL‐1β production, and inflammation. NLRP3 activation requires two signals. The first leads to transcriptional regulation of specific genes related to inflammation, and the second is triggered when pathogens, toxins, or specific compounds damage cellular membranes and/or trigger the production of reactive oxygen species (ROS). Here, we assess the requirement of the first signal (priming) for the act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…Importantly, inflammasome activation can only be robustly achieved upon previous priming (Supplementary Fig. 3a), just as observed in others studies 27,43,44 . The presence of the virus did not affect the production of inflammasome-independent cytokines, such as TNF-α (Fig.…”
Section: Resultssupporting
confidence: 72%
“…Importantly, inflammasome activation can only be robustly achieved upon previous priming (Supplementary Fig. 3a), just as observed in others studies 27,43,44 . The presence of the virus did not affect the production of inflammasome-independent cytokines, such as TNF-α (Fig.…”
Section: Resultssupporting
confidence: 72%
“…The reason why the mRNA levels did not follow the protein levels was not clear, and previous studies have demonstrated similar results to ours 54 . Nevertheless, transcription‐independent roles of the priming signal have been recently shown 55 . LPS can prime the NLRP3 inflammasome activation independently of NLRP3 induction, once a short‐term pre‐treatment with LPS did not change NLRP3 expression 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, inflammasome assembly and signaling are closely associated with the physiopathology of leishmaniasis [ 30 32 ]. We and others have shown that the NLRP3 inflammasome is protective and contributes to restricting L. amazonensis parasite replication in macrophages as well as in vivo [ 30 , 33 , 34 ]. The canonical NLRP3 inflammasome promotes IL-1 β and IL-18 activation through the engagement of NLRP3, ASC, and caspase-1 activation.…”
Section: Discussionmentioning
confidence: 99%